AS RELAÇÕES INTERPESSOAIS NA CONSTRUÇÃO DA EAD SOB UM ENFOQUE ETNOMETODOLÓGICO E MULTIRREFERENCIAL - Nunes, Mônica Ferreira (2009)
The present study proposes an understanding of the interpersonal relationships between subjects involved in the construction and execution of the pedagogic Project of Distance Learning under an ethno methodological and multi-referential perspective of education.We propose identifying how relationships are established in Distance Learning, which its organizational agents are and how they interact in the organization of the work, since Distance Learning requires an array of professionals with different kinds of knowledge so as to achieve its goals. We used as reference Distance Learning Courses at UNESP and through the use of observation, reports, questionnaires and interviews, we intend to identify how subjects see and understand themselves in the process and how they understand and recognize other subjects in the development of activities of such course. Using as reference the steps taken in the elaboration and realization of a video-conference, we aim at recognizing the communication process within the group of technicians, managers, professors and learners in the organization, as well as analyzing connections and ruptures, the wide-range actions and the importance of its functions on a daily basis.(AU)